ANALYSIS OF EMPLOYEE EMPOWERMENT STRATEGY MODEL WITH EMPLOYEE ENGAGEMENT: A STUDY IN THE COMMERCIAL BANKING SECTOR IN INDONESIA - Islamuddin, Islamuddin; Hadikusumo, Reina A.; Lestari, Deara Shinta (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
This research aims to investigate the impact of employee empowerment, job crafting, and work-life balance on employee engagement in the Indonesian commercial banking sector. Using a quantitative approach with an explanatory design, data were collected through a survey of 150 commercial bank employees selected using a purposive sampling technique. The analysis was conducted using the Structural Equation Modeling (SEM) method, based on Partial Least Squares (PLS), to examine the relationship between latent variables. The research results indicate that the three independent variables have a positive and significant impact on employee engagement, with job crafting being the most dominant predictor, followed by employee empowerment and work-life balance. These findings confirm that employee engagement can be increased through empowerment, flexibility, and work-life balance strategies that are more adaptive to the demands of the banking sector. Practically, this research provides implications for banking management to strengthen empowerment policies, provide employees with space to design their work roles, and create a work climate that supports a balance between professional and personal demands, thereby increasing organizational involvement and performance sustainably.